Smart MPP Public Service Innovation at the Investment and PTSP Service of Probolinggo City - Satunggale Kurniawan kamil; Indrawati Indrawati (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. The public often encounters several challenges in managing permits, such as slow processing times and inconsistent adherence to service procedures by employees. Issues include a lack of focus on public service duties, prioritization of personal interests over community needs, inconsistent application of rules, and uncertain timelines for permit completion. These challenges highlight the need for enhanced public service systems, especially given the rapid advancement of information technology and growing socio-economic disparities. To address these issues, the Probolinggo City government has initiated the MPP (Mall Pelayanan Publik) Smart Public Service Innovation at the Probolinggo City Investment and PTSP Office to improve service efficiency and reliability. Purpose. This study aims to analyze the implementation of the MPP Smart Public Service Innovation in Probolinggo, evaluating its effectiveness in overcoming service challenges and improving the public’s experience in permit management. The goal is to identify how this innovation can serve as a model for sustainable, citizen-focused public service. Method. A qualitative research method was employed, focusing on in-depth exploration of social phenomena and human behavior related to public service. This approach enabled a comprehensive understanding of experiences, perceptions, and motivations of stakeholders, including citizens and employees at the Probolinggo City Investment and PTSP Office, to gain insight into the impact of the Smart Public Service Innovation on service quality. Results. The study reveals that the MPP Smart Public Service Innovation has significantly improved the speed and efficiency of the permitting process, reduced socio-economic disparities in service accessibility, and enhanced employee compliance with service protocols. The initiative has led to a more structured and reliable service experience, addressing many of the previously identified challenges in permit management. Conclusion. The MPP Smart Public Service Innovation in Probolinggo City demonstrates the potential of technology-driven approaches to improve public service delivery. By focusing on consistency, accountability, and citizen satisfaction, this innovation supports the goal of providing sustainable and equitable public services. These findings offer a valuable framework for other regions aiming to optimize their public service systems.